EARTHQUAKE HYPOCENTER RELOCATION ANALYSIS USING DOUBLE DIFFERENCE METHOD IN THE SORONG FAULT, WEST PAPUA, INDONESIA - Irfan Saleh, M.
The Sorong fault is one of the active faults in Papua. In the historical record of seismicity several earthquake have occurred in this area, one of which was the earthquake on September 24 2015 with a magnitude of 6.3 Ms. These condision make the study of seismology important, especially the analysis of earthquake hypocenters which can be used to mitigate earthquake hazards. In this Final Project the method used for relocating the hypocenter of an earthquake is the Double Difference method and using earthquake data from 31 December 2018 to 31 July 2022. Double Difference Method can minimize errors due to the velocity structure which has not been modeled on the results of the initial parameter determination. For this reason, it is necessary to update the hypocenter using station correction. The seismicity distribution obtained from the relocation results can provide an overview of the segmentation of the Sorong Fault. Based on the results obtained, it shows that the Sorong Fault with the Dampir Segment has a focal depth of about 20 km, the Sagewin Segment about 25 km, the Klararea Segment about 20 km, the Mega Omnowi Segment about 20 km, the Anita Segment about 25 km, the Meuni and Warjori Segments about 20- 25km.